Reconsider this summer`s Olympic and Paralympic games - Shimizu, K.; Sridhar, D.; Taniguchi, K.; Shibuya, K. (British Medical Journal, 2021)
The government of Japan and the International Olympic Committee are determined to hold the Olympic Games in Tokyo this summer. In February 2021, G7 leaders also supported Japan`s commitment to holding the Olympics and Paralympics in Tokyo (Tokyo 2020) "in a safe and secure manner … as a symbol of global unity in overcoming covid-19."1 While the determination is encouraging, there has been a lack of transparency about the benefits and risk, and international mass gathering events such as Tokyo 2020 are still neither safe nor secure. The world is still in the middle of a pandemic. SARS-CoV-2 variants are an international concern, causing a resurgence of covid-19 globally.2 We must accelerate efforts towards containing and ending the pandemic by maintaining public health and social measures, promoting behaviour change, disseminating vaccines widely, and strengthening health systems. Substantial scientific advancements have occurred over the past year, but vaccine rollout has been inequitable, reducing access in many low and middle income countries. Huge uncertainty remains about the trajectory of the pandemic.3 Although a special scheme for vaccinating athletes—marshalled by the International Olympic Committee4—may help save lives, it could also encourage vaccine diplomacy, undermine global solidarity (including the Covax global access scheme), and promote vaccine nationalism. Full transparency and clear lines of accountability are critical in any scheme to vaccinate athletes. Furthermore, prioritising athletes over essential workers at high risk in low and middle income countries raises ethical concerns that must be addressed.